G404(P) Catching up with the 21st century (through charity!): is a computerised clinical jobs book superior to a paper based jobs diary?. (12th March 2018) - Beatty, C; Simpson, L; Javed, MS; Javed, MS; White, R; Baacha, Z; Saleem, Z
Abstract : Background: With increasing workload and reducing length of stay, a robust system was needed to keep track of outstanding clinical jobs regarding patients whose early discharge was made possible by the on-site presence of senior decision makers. A paper based diary initially proved successful and results were presented as a (P) at the RCPCH annual conference 2015. However, this system did not keep up with demands and posed several clinical governance challenges. Therefore, a computerised network based system (PaedsTMS) was developed with help of employees of a multinational technology firm as a charity project. Aims: To assess the effectiveness and quality of jobs recording and completion, before and after the introduction of PaedsTMS. Methods: PaedsTMS was introduced in June 2017 after an initial audit of the existing paper based system. The project was led by a registrar under guidance of a consultant paediatrician. A team of champions from medical, nursing and clerical background was assembled. Team discussions were done on messaging apps. Training was accomplished face to face and by video tutorial on YouTube. PaedsTMS was run parallel to the existing system for two weeks. Two audits were completed after introduction of PaedsTMS in July and September 2017. We looked at the percentage of tasks added to PaedsTMS, percentage of tasks added with sufficient clinical information, percentage of outstanding tasks completed and percentage of tasks completed within due date. The results were compared with pre-PaedsTMS introduction audit. Results: The re-audit showed significant improvements as depicted in table 1 below: Conclusion: The computerised system has significantly increased the quality of clinical details recorded with jobs as well as their timely completion whilst providing a clear audit trail to satisfy clinical governance standards.